Eksplorasi Kearifan Ekologis dalam Cerita Rakyat Putri Lopian dari Sumatera Utara: Perspektif Ekokritik - Diah Kusyani; Sukma Adelina Ray; Mutia Febriyana; Dian Ahyunnisa (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study examines the ecological wisdom in the North Sumatera folktale, Putri Lopian from an ecocritical perspective. Folktales, as part of oral literature, often contain social values ​​and norms about human interaction with nature. This study aims to analyze the ecological wisdom contained in the Putri Lopian folktale through an ecocritical approach. The research method used is descriptive qualitative with an ecocritical analysis approach. Data were obtained from literature studies and the text of the folktale. The results show that the Putri Lopian folktale contains ecological wisdom values, which reflect an awareness of the importance of maintaining ecosystem balance and respecting nature. This story can be categorized as apocalyptic literature because it depicts natural phenomena such as earthquakes, low tides, and powerful waves. In addition, this story contains five of Greg Garrard's six ecocritical concepts, namely wilderness, apocalypse, dwelling, animals, and earth. This ecocritical study contributes to a deeper understanding of ecological wisdom in the context of local North Sumatera culture. This story serves as a basis for promoting environmental awareness through a literary approach.